2020
DOI: 10.5607/en20014
|View full text |Cite
|
Sign up to set email alerts
|

Death-associated Protein Kinase 1 Phosphorylates α-Synuclein at Ser129 and Exacerbates Rotenone-induced Toxic Aggregation of α-Synuclein in Dopaminergic SH-SY5Y Cells

Abstract: The formation of Lewy bodies (LBs), intracellular filamentous inclusions, is one of the hallmarks of Parkinson's disease (PD). α-Synuclein is the main component of LBs and its abnormal accumulation contributes to the pathogenesis of PD. Direct phosphorylation of α-synuclein at multiple Ser/Tyr residues is known to induce its aggregation, consequently promoting LB formation. Death-associated protein kinase 1 (DAPK1), originally identified as a positive mediator of γ-interferon-induced programmed cell death, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Lewy bodies can activate surrounding microglia, promote the release of inflammatory mediators, and aggravate neuronal injury ( 38 ). A small fraction of α-synuclein is phosphorylated at the S129 site (<4%) in healthy brains, but it has been observed to be accumulated (~90%) in the brains of patients with PD ( 39 ). Therefore, pS129 α-synuclein was used as a marker to evaluate the pathological changes associated with α-synuclein.…”
Section: Resultsmentioning
confidence: 99%
“…Lewy bodies can activate surrounding microglia, promote the release of inflammatory mediators, and aggravate neuronal injury ( 38 ). A small fraction of α-synuclein is phosphorylated at the S129 site (<4%) in healthy brains, but it has been observed to be accumulated (~90%) in the brains of patients with PD ( 39 ). Therefore, pS129 α-synuclein was used as a marker to evaluate the pathological changes associated with α-synuclein.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that BDNF induction at least in part might contribute to the neuroprotective effects of Boswellia extract. These also highlight the pleiotropic actions of AMPK in Previous studies demonstrated that rotenone treatment elevated numbers of α-synuclein cytoplasmatic inclusions in neurons and α-synuclein phosphorylation [58][59][60]. A more direct link between apoptosis and DNA damage has been described in relation to α-synuclein.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies demonstrated that rotenone treatment elevated numbers of α-synuclein cytoplasmatic inclusions in neurons and α-synuclein phosphorylation [ 58 60 ]. A more direct link between apoptosis and DNA damage has been described in relation to α-synuclein.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that EVs acts as a key mediator in the central nervous system communication that actively responds to nervoual damage, mediating inflammation and inflammation-related neuroprotection ( Delpech et al, 2019 ). Lewy body formation (LBs) is the underlying neuropathological feature of PD ( Shin and Chung, 2020 ), mainly composed of αlpha-synuclein. Under normal conditions, α-synuclein exists in a soluble form.…”
Section: Nerroprotection Of Exosomal Non-coding Rnamentioning
confidence: 99%